Public Services Advertising Community Movement Program “GERMAS” Public Health, Batu Bara District through Radio Odan FM - Sahdin Hasibuan; Erwan Efendi; Arief Rahman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to find and study about public services advertising community movement program “GERMAS” public health.  This research is in the form of field research. Field research is research that is aimed directly at the location of the research to be studied, namely in a community, agency or company to search for data and then observe and conclude. Based on the results of the discussion in the previous chapter, it can be concluded that the public service advertisement broadcast of the GERMAS program broadcast by Odan FM Radio is effective, because listeners find it helpful to have information in the form of advertisements delivered through Odan Radio broadcasts, where many people follow several the points in the GERMAS program, although there are still people who do not know about and participate in this GERMAS program, where there are deficiencies felt by the Health Office in delivering the GERMAS program in the community.